Threat of attacks of Ixodes ricinus ticks (Ixodida: Ixodidae) and Lyme borreliosis within urban heat islands in south-western Poland - Alicja Buczek; Dariusz Ciura; Katarzyna Bartosik; Zbigniew Zając; Joanna Kulisz (Parasites & Vectors, 2014)
Abstract Background The increased incidence of Lyme disease in Europe necessitates permanent monitoring of the occurrence and activity of its vector. Therefore, in this study, we have investigated the presence and seasonal activity of Ixodes ricinus ticks in various habitats of a large industrial region in south-western Poland in correlation with environmental factors present in urban heat islands. Additionally, the risk of borreliosis in this part of Poland has been assessed. Methods The investigations were carried out at two-week intervals between April and October 2001 and 2002. Ticks were collected from four localities in Upper Silesia, i.e. in a city park (CH), on the outskirts of two large cities (KO, MI), and in a forest (KL). We analysed the impact of temperature and humidity measured during the collection period in the I. ricinus habitats, the climatic conditions prevailing in the study area, and the degree of environmental contamination on the abundance and activity of these ticks in the respective sites. The degree of borreliosis risk in the region was determined on the basis of the results of research on the prevalence of Borrelia burgdorferi s.l. in ticks and reports from sanitary-epidemiological stations. Results In total, 2061 I. ricinus ticks, including 606 nymphs and 1455 adults, were collected in the study area. The number and activity of the ticks varied during the collection in the different sites. In the urban locality CH, tick abundance was the lowest (455 throughout the investigation period), and the seasonal activity of females was unimodal and persisted for as long as 4 months. In the suburban localities KO and MI, tick abundance was higher (485 and 481 specimens, respectively) and the activity of females was unimodal. The highest abundance (640 ticks) and a bimodal pattern of female activity were reported from the forest locality KL. In all the localities, the activity of nymphs was unimodal. Humidity was found to be a factor influencing I. ricinus abundance and activity, whereas temperature did not affect their number and behaviour significantly. The climate parameters within the urban heat islands noted during the investigations contributed to dispersal of dust and gas pollutants. The analysis of the data reveals that there is a risk of borreliosis in the entire study area; however, it is higher in the urban localities than in the suburban sites. Conclusions Environmental conditions (habitat, climate, and dust and gas pollution) prevailing within urban heat islands may exert an impact on tick abundance and activity and the prevalence of Lyme disease in the study area. The greatest effect of the environmental factors on ticks was found in the city park, where the risk of human infection with B. burgdorferi s.l. spirochetes is the highest as well.